REGIONAL AUTONOMY : SYTEMATIC LITERATURE REVIEW - Dany Try Hutama Hutabarat; Anisyah; Tiara Divani Sary; Eka Widya Lestari; Riski Adila Manja; Handayani (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2022)
Regional autonomy refers to the authority that regulates the community's interests or acts as a regulator in areas where the federal government empowers local governments to manage their own government. This research technique utilizes five book sources in order to learn about regional autonomy, its various forms, and legal foundations. Community engagement in governance, particularly at the village level, is one of the foundations of regional autonomy that requires attention in this regard. Concerning the village government system's role in development implementation, many village development initiatives have been conceived and determined primarily on considerations and techniques from above, without involving the community being developed.